Graduate public health student learning experiences, social connectedness, and mental health during COVID-19: pedagogical implications for public health academic departments - Agroia, Harit; Berkowitz, Rachel; Carter, Andrew; Gomez, Vicky; Allen, Monica (Frontiers in Public Health, 2024)
The COVID-19 pandemic impacted college student learning both globally and nationally. Current literature points to decreases in social connectedness, adverse mental health outcomes, and decreased overall learning outcomes; however, there are no findings from higher education institutions within the Bay Area, California. There are also no studies that examine the COVID-19 impact among public health graduate students, especially to understand how the pandemic renewed their interest in the field. The purpose of this study was to investigate the effects of COVID-19 on graduate student learning experiences, social connectedness and mental health within the Master of Public Health program at San José State University in San Jose, California. We employed a convergent mixed-methods design using a survey that quantitatively assessed student learning experiences through a retrospective pre-and post-design, and a semi-structured interview guide that qualitatively assessed student learning experiences and its relationship with mental health and social connectedness using a phenomenological design. Data were collected between September 2022 - June 2023 and analysis was performed using descriptive statistics and thematic analysis. A total of 22 students completed the survey and four participated in follow-up semi-structured interviews. Of the 22, 12(55%) were among the 18–29-year age group, 9(53%) identified as Asian, 21(95%) identified as female, and 9(41%) identified as a first-generation college student. When comparing survey responses, the median change in learning experiences pre and during-pandemic were statistically significant across several areas such as student ability to stay organized (p<0.0001), participate actively in class (p<0.001), retain course material (p<0.0001), collaborate with peers (p<0.0001), and maintain a sense of connection with their cohort (p<0.0001) and broader campus community (p<0.0001). Semi-structured interviews further revealed the following six themes: (1) Consistent faculty support; (2) Sense of community; (3) Reduced social connectedness; (4) Impact on mental health; (5) Deeper public health understanding; and (6) Facilitators and barriers. Educational practitioners are encouraged to offer hybrid academic programs and establish resource infrastructures that provide students with social and mental wellness support when transitioning to different learning modalities.